Analysis of the Quality of Achievement Test Questions for the Arabic Language Subject at Mutiara Global Integrated Islamic Junior High School - Ayu Afni Yurmita; Dadang Firdaus (INTIFA: Journal of Education and Language, 2025)
This research aimed at analyzing the summative test item quality on Arabic Language subject at Integrated Islamic Junior High School of Mutiara Global as an effort to ensure that questions used were in accordance with good evaluation standards. The analysis focused on validity, reliability, difficulty level, and discriminative power. Quantitative descriptive method was used in this research utilizing data from test items, answer keys, and student work results. The research findings showed that 14 test items were on correct question category, and 11 items were on incorrect question category. In this case, the validity of the analyzed question items was on high category. The reliability of the questions was on high category, while the level of difficulty of the questions showed not yet ideal distribution. The discriminative power of most of the questions was good, but there were some questions requiring improvement. In addition, the difficulty levels of the questions were based on difficult, easy, and hard questions. In fact, there was no question on difficult question category, there were 24 questions on moderate question category, and there was a question on easy question category. This research was expected to contribute to increase the quality of evaluation in Arabic language learning.